2+6h=10+3h

Simple and best practice solution for 2+6h=10+3h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+6h=10+3h equation:


Simplifying
2 + 6h = 10 + 3h

Solving
2 + 6h = 10 + 3h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-3h' to each side of the equation.
2 + 6h + -3h = 10 + 3h + -3h

Combine like terms: 6h + -3h = 3h
2 + 3h = 10 + 3h + -3h

Combine like terms: 3h + -3h = 0
2 + 3h = 10 + 0
2 + 3h = 10

Add '-2' to each side of the equation.
2 + -2 + 3h = 10 + -2

Combine like terms: 2 + -2 = 0
0 + 3h = 10 + -2
3h = 10 + -2

Combine like terms: 10 + -2 = 8
3h = 8

Divide each side by '3'.
h = 2.666666667

Simplifying
h = 2.666666667

See similar equations:

| 47.25x+0.0484=-172.5x+0.4465 | | 24w+(-10)=15 | | 5*3+5*6= | | 90+45=x | | -9x+12=7x+24 | | 5x-18*4=-36 | | A=2(1+w) | | 200m-75m+52800=56100-150m | | 5x-18*4x=-36 | | 32(20x-60)=16(40-x) | | 3(x-5)=2x+9 | | 0.5x=-x+11 | | 2x+4=4x+10 | | 8+z=14 | | 5x-18*x=-36 | | 8x+x=63 | | 2x+4=4x+19 | | -0.125=2(x-1) | | 56t^2-19t=15 | | 32-0.2c=1 | | -13=16+m | | 174x=180(x-700) | | -12n+16=-8n-16 | | 2-p=p+2 | | 5x(x-6)=9+(x-2)(5x-2) | | 67=17+5x | | 6(x+3)=12x-12 | | 10x*20x-41*2=4 | | 3x-5(x+2)=8x+10 | | (5x+4)-2(x+1)= | | 8(60-80x)=112 | | 6y+39=-9(y-1) |

Equations solver categories